Electrorefining of base metal refinery residue copper alloy for platinum group metal recovery - Kruyswijk, Lizelle (Centre for Bioprocess Engineering Research, 2014)
Secondary leach concentrate (SLC) is an important bleed stream for minor elements from Anglo Platinum’s Base Metal Refinery (BMR) which produces copper nickel and cobalt sulphate. It contains mainly sulphur, iron jarosites, unleached base metals and platinum group metals (PGMs), which makes the treatment of SLC necessary. The SLC is currently toll-refined at Umicore’s Hoboken smelter and refinery to recover revenue from entrapped valuable metals. This method of treatment results in excessively high costs due to high transport and toll refining expenses as well as penalties. Thus, an in-house method of treatment by Anglo Platinum itself would prove beneficial in that it would eliminate these excessive costs and also provide a method of treatment in the event of residues exporting becoming banned or strongly penalised in future. Therefore, a method for treating SLC in-house is investigated. The first stage of the proposed treatment method involves a pyrometallurgical process where the removal of amphoterics by oxidative fuming, followed by reduction to recover base metals from the slag takes place. The PGMs are reported mainly to the metal alloy phase along with the base metals during this process. The project discussed in this report deals with the treatment of this furnace alloy which is referred to as Cu alloy. The Cu alloy is used to produce anodes to be applied to an electrorefining application for the recovery of Cu as a Cu cathode and PGMs in the form of anode slimes. Spent electrolyte from the BMR copper electrowinning section adjusted to specific pH and Cu concentration is used as electrolyte to which dissolvable metals (such as Ni and Fe) are recovered.